OʻZBEKISTONDA YASHIL LOGISTIKANI RIVOJLANTIRISH ISTIQBOLLARI (Marketing Jurnali, 2025)
This paper analyzes the development prospects of green logistics in Uzbekistan based on global best practices. The green logistics models of major corporations such as UPS, Amazon, IKEA, Alibaba, Tesla, and DHL are examined, and their applicability to Uzbe kistan is assessed. The study proposes recommendations for supply chain digitalization, blockchain and IoT adoption, and energy -efficient as well as recyclable materials utilization. The research findings are based on Multi -Criteria Decision Analysis (MCDA ), Life Cycle Assessment (LCA), and SWOT analysis, allowing for the identification of strategic priorities for sustainable logistics development.
Keywords: yashil logistika; taʼminot zanjiri; raqamlashtirish; blokcheyn; IoT; qayta ishlanadigan materiallar; energiya samaradorligi; MCDA; LCA; SWOT -tahlil